Baud rate variations effect on virtual channel based on PIC microcontroller - Sarmad K. Ibrahim; Hussein M. Hathal; Riyadh A. Abdulhussein (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Recent year in the world the real applications, usually needed only a few key features of Universal Asynchronous Receiver Transmitter (UART). It is a type of serial communication protocol, which improves the problem of parallel communication and develops effectively in several services. This paper presents a transceiver system based on PIC microcontroller. It also presents software designs to transmit and receive data through the virtual channel. The system is designed to study the effects of baud rate variations between transmitter and receiver for noise and noiseless AWGN channel. The system has been simulated by Proteus simulator version 8.1, and then tested successfully at baud rates (2400, 4800, 9600, and 19200) bps. Simulation results show that the error rate has zero values at the desired baud rate value, and also, at the adjacent values. Thus, the zero level of error rate is increased by increasing baud rate values, which fixed by the transmitter and vice versa.